Assessing the adaptive capacity of urban form to climate stress: a case study on an urban heat island. (2nd April 2019) - Xu, Lilai; Cui, Shenghui; Tang, Jianxiong; Nguyen, Minh; Liu, Jiahui; Zhao, Yanchuang
Abstract: Urban land planning shapes the urban form and is considered to be one of the many tools important for climate adaptation. Yet there is little knowledge about the adaptive capacity of urban forms to climate stress, or of an appropriate assessment method. Through a case study on the urban heat island (UHI) in Xiamen City, China, we propose a novel approach that integrates several aspects to assess the adaptive capacity of urban form to climate stress. These aspects include the calculation of urban form, the determination of climate stress and land use modeling. Our results demonstrate that this approach is applicable for assessing the adaptive capacity of urban form in the historical, current and future multitime scales. Both urban planning aspects (e.g. population density, land use mix, road density and percentage of green open space) and landscape features (e.g. shape complexity, contiguity and compactness) are found to be key urban form drivers affecting UHI. The adaptive capacity of the urban form to UHI in Xiamen City has been declining dramatically, and is expected to continue to decline in the future as long as adaptation continues to not be integrated in urban land use planning. Our analysis suggests that urban managers need to review the past development model of land use and rethink the current approach to urban planning: most urgent is the need to take full account of adaptation in future land use planning and implementation, so as to enhance climate resilience.